2019
DOI: 10.2188/jea.je20180098
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Metal Levels in Whole Blood and IgE Concentrations in Pregnant Women Based on Data From the Japan Environment and Children’s Study

Abstract: BackgroundMetal exposures could possibly affect allergic responses in pregnant women, although no studies have yet shown a clear relationship between the two, and such exposures might also affect the development of allergic diseases in children.MethodsWe investigated the relationship between metal concentrations in whole blood and immunoglobulin E (IgE; total and specific) in 14,408 pregnant women who participated in the Japan Environment and Children’s Study. The subjects submitted self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… 11 Findings from studies of the general population have also suggested that allergic sensitization may be associated with increases in disease susceptibility. 12 , 13 Fetal and early postnatal exposures to arsenic, cadmium, lead, mercury, and chromium may be important factors associated with immunotoxic effects. 14 , 15 Because exposure to chemicals in the environment is complex and part of the exposome associated with health and disease, 16 this birth cohort study aimed to investigate the association between prenatal exposure to multiple metals and the risk of atopic dermatitis in young children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Findings from studies of the general population have also suggested that allergic sensitization may be associated with increases in disease susceptibility. 12 , 13 Fetal and early postnatal exposures to arsenic, cadmium, lead, mercury, and chromium may be important factors associated with immunotoxic effects. 14 , 15 Because exposure to chemicals in the environment is complex and part of the exposome associated with health and disease, 16 this birth cohort study aimed to investigate the association between prenatal exposure to multiple metals and the risk of atopic dermatitis in young children.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of disease may involve activation of the aryl hydrocarbon receptor and the NFE2L2 gene . Findings from studies of the general population have also suggested that allergic sensitization may be associated with increases in disease susceptibility . Fetal and early postnatal exposures to arsenic, cadmium, lead, mercury, and chromium may be important factors associated with immunotoxic effects .…”
Section: Introductionmentioning
confidence: 99%
“…Asthma patients who are allergic to ticks. In general, a positive correlation was observed between the strength of the skin response and higher serum IgE levels (36). Allergens are environmental antigens that can stimulate the production of certain IgE antibodies.…”
Section: Discussionmentioning
confidence: 99%